Odnos med stopnjo zadovoljstva in zvestobo gostov v slovenskih hotelih - Zabukovec Baruca, Petra (Naše gospodarstvo, 2012)
This article examines the relationship between satisfaction and loyalty of hotel guests. From the hotel's perspective, it is cheaper and more beneficial to create a loyal guest than seek out new ones; therefore, this paper focuses on satisfaction as an influential factor in customers' re-visit of a hotel. Using an empirical study, we examine the connection between guests who are more satisfied with the hotel and their intention to re-visit the hotel. However, we are also interested in differences in satisfaction level and intention to re-visit among guests who visit once, twice or more. A higher level of guest satisfaction makes customers more likely to repurchase, which leads to guest loyalty, commitment to partnership activities and positive recommendations of the hotel.
Keywords: Slovenia; Slovenija; hoteli; hotelirstvo; gostje; zadovoljstvo